1974
DOI: 10.1073/pnas.71.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Thymocytes in Sera of Patients with Schizophrenia

Abstract: Sera from healthy people and from patients with schizophrenia were heated at 560 for 30 min and then kept at 4'. These sera were then tested for cytotoxicity and by the indirect immunofluorescerice method with thymocytes, bone-marrow cells, and lymph-node cells of adult C3H mice. The cytotoxicity index for mouse thymocytes of sera from 60 healthy donors ranged from 0.00 to 0.4, with an average of 0.08. That of sera from 35 patients with schizophrenia ranged from 0.29 to 0.91, with an average of 0.71. The cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Figure 1 shows that in the patient group there is an accumulation of subjects with high ATA levels, from 0.46 to 1.0. This corresponds with previous findings (Luria and Domashneva, 1973; of high blood serum ATA in schizophrenia patients. Further analysis revealed that the serum ATA of patient group 1 was significantly higher than that of the matching control (0.36 ± 0.06 and 0.11 ± 0.02, P < 0.001), whereas in group 2, we found no differences between the patients and healthy donors ( Table 3).…”
Section: Characteristics Determined At the Institute Of Virology Slovsupporting
confidence: 93%
“…Figure 1 shows that in the patient group there is an accumulation of subjects with high ATA levels, from 0.46 to 1.0. This corresponds with previous findings (Luria and Domashneva, 1973; of high blood serum ATA in schizophrenia patients. Further analysis revealed that the serum ATA of patient group 1 was significantly higher than that of the matching control (0.36 ± 0.06 and 0.11 ± 0.02, P < 0.001), whereas in group 2, we found no differences between the patients and healthy donors ( Table 3).…”
Section: Characteristics Determined At the Institute Of Virology Slovsupporting
confidence: 93%
“…In a PNAS paper, autoantibodies against thymocytes are also noted in serum of schizophrenia patients. (Luria and Domashneva 1974) Thus, the autoantigen of schizophrenia might also be AchR.…”
Section: Discussionmentioning
confidence: 99%
“…The results of some authors would suggest that immunologic events are involved [1][2][3][4][5]. Thus in schizophrenic patients [1] an in creased number of multiplying lymphocytes in the peripheral blood has been found by autoradiography, detecting cells in the S phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 94%
“…Thus in schizophrenic patients [1] an in creased number of multiplying lymphocytes in the peripheral blood has been found by autoradiography, detecting cells in the S phase of the cell cycle. A depressed response to phytohemagglutinin stimulation of periph eral blood lymphocytes has also been seen [2][3], Antibodies reacting with mouse thy mocytes have been found either by immu nofluorescence staining or in a cytotoxicity assay [3][4][5]. (The mouse thymus shares an antigen with mouse and human brain).…”
Section: Introductionmentioning
confidence: 99%